Role of Janus kinase 1 and signal transducer and activator of transcription 3 in vitiligo - Samaka RM; Basha MA; Menesy D (Dove Medical Press, 2019)
Rehab M Samaka,1 Mohammed A Basha,2 Dina Menesy31Department of Pathology, Faculty of Medicine, Menoufia University, Shibīn al Kawm, Egypt; 2Department of Dermatology, Andrology and STDs, Faculty of Medicine, Menoufia University, Shibīn al Kawm, Egypt; 3General Organization for Teaching Hospitals and Institutes, Damanhour Medical National Institute, Damanhour, EgyptBackground: Vitiligo is an acquired autoimmune skin disorder. The often-visible lesions of vitiligo have a major impact on patients’ quality of life and the results of the treatment regimens on offer are unsatisfactory, so there is a need for new therapeutic regimens. Recent advances in vitiligo pathogenesis have led to recognition of the importance of the JAK–STAT pathway as an attractive therapeutic option.Purpose: To evaluate role of JAK1 and STAT3 in vitiligo.Methods: This prospective case–control study was carried out on 35 patients presenting with vitiligo and 20 apparently healthy age- and sex-matched volunteers. Skin biopsies from controls and cases were taken for histopathological and immunohistochemical JAK1 and STAT3 evaluation.Results: Epidermal and dermal overexpression of STAT3 was noted in lesional skin compared to the other groups (P=0.02 and P<0.001, respectively). There was a positive correlation between dermal expression of JAK1 and dermal expression of STAT3 (r=0.52, P=0.004).Conclusion: In conjunction, JAK1 and STAT3 might be involved in the pathogenesis of vitiligo. This could open the gate for the use of JAK1 and STAT3 inhibitors as new targeted therapy for vitiligo.Keywords: JAK1, STAT3, vitiligo, immunohistochemical